2011
DOI: 10.1111/j.1365-2664.2011.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophytes respond to reach‐scale river restorations

Abstract: Summary1. In recent years, river restoration science has been searching for biological indicators of improvement in the physical habitats of streams. To date, research has mainly focused on the use of fish and macroinvertebrates as indicators. Despite their importance in aquatic ecosystems, the response of macrophytes to habitat restoration has been rarely studied. 2. We investigated the macrophyte communities of 40 restored river reaches in the lowland and lower mountainous areas of Germany. Each restored rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 50 publications
(59 reference statements)
3
74
3
Order By: Relevance
“…Very rarely has this fluvial dynamism been taken into consideration in the design of restoration projects and temporal data documenting restoration effects on fluvial processes are missing. Even though the number of river restorations has increased over the last several decades in both Europe and North America (Bernhardt et al, 2005;Feld et al, 2011;Lorenz et al, 2012), studies providing conclusive empirical evidence of its effects are lacking (Bernhardt and Palmer, 2011). Several published reviews provide almost no evidence of a long-term (+5 years) positive effect of river restoration on biotic communities (Roni et al, 2008;Miller et al, 2010;Feld et al, 2011), albeit Lorenz et al (2012) in a recent study found a longer term positive response of macrophytes to restoration measures.…”
Section: Introductionmentioning
confidence: 99%
“…Very rarely has this fluvial dynamism been taken into consideration in the design of restoration projects and temporal data documenting restoration effects on fluvial processes are missing. Even though the number of river restorations has increased over the last several decades in both Europe and North America (Bernhardt et al, 2005;Feld et al, 2011;Lorenz et al, 2012), studies providing conclusive empirical evidence of its effects are lacking (Bernhardt and Palmer, 2011). Several published reviews provide almost no evidence of a long-term (+5 years) positive effect of river restoration on biotic communities (Roni et al, 2008;Miller et al, 2010;Feld et al, 2011), albeit Lorenz et al (2012) in a recent study found a longer term positive response of macrophytes to restoration measures.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible forms ensure colonization of unoccupied spaces, unavailable for other species of macrophytes (O'Hare et al 2011). Moreover, submerged vegetation has a significant impact on the accumulation of fine sediments, reduces erosion, increases retention, preserves water clarity and improves its quality (Horippila & Nurminen 2003;Kleeberg 2010;O'Hare et al 2011;Lorenz et al 2012). We showed the relationships between water velocity and other environmental factors, such as the depth of water and type of substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, morphological adaptations, such as reduction in the leaf number, are the result of aquatic plant response to hydrodynamic stress (Puijalon et al 2007). Growth forms of aquatic plants can be used as tools for the habitat modification assessment and monitoring of ecological status of different rivers types (Gurnell et al 2010;Lorenz et al 2012;Vukov et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although recolonisation of macrophytes is a common goal of restoration in Europe (Lorenz et al 2012), they are rarely considered in this context in Australian streams. This study indicates the potential for positive growth response of some submerged native macrophyte species to stream degradation in seasonally-flowing streams, and demonstrates that these plant assemblages can support a more abundant and diverse aquatic fauna in reaches where riparian vegetation is degraded or absent.…”
Section: Management Implicationsmentioning
confidence: 99%